2012
DOI: 10.4049/jimmunol.1103771
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps Entrap and KillBorrelia burgdorferiSensu Stricto Spirochetes and Are Not Affected byIxodes ricinusTick Saliva

Abstract: Lyme disease is caused by spirochetes of the Borrelia burgdorferi sensu lato complex. They are transmitted mainly by Ixodes ricinus ticks. After a few hours of infestation, neutrophils massively infiltrate the bite site. They can kill Borrelia via phagocytosis, oxidative burst, and hydrolytic enzymes. However, factors in tick saliva promote propagation of the bacteria in the host even in the presence of a large number of neutrophils. The neutrophil extracellular trap (NET) consists in the extrusion of the neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 34 publications
0
41
1
Order By: Relevance
“…However, the staining technique they used would probably not identify basophils. On the other hand, a recent study [19] of immune responses to Ixodes scapularis saliva emphasized the role of neutrophils in preventing Borrelia infection.…”
Section: Ticks and Ige Antibody Responsesmentioning
confidence: 99%
“…However, the staining technique they used would probably not identify basophils. On the other hand, a recent study [19] of immune responses to Ixodes scapularis saliva emphasized the role of neutrophils in preventing Borrelia infection.…”
Section: Ticks and Ige Antibody Responsesmentioning
confidence: 99%
“…burgdorferi has been shown to induce the release of NO from macrophages (25) and recruitment of macrophages and neutrophils to organs where it disseminates (22,24,83). However, previous studies showed that inhibition of iNOS using N G -L-monomethyl arginine (LMMA) does not significantly affect the bacterial burden in the heart and joint of C3H/HeJ or BALB/c mice infected with B. burgdorferi (84) and has only a minor effect on survival of the bacterium in the presence of macrophages (25).…”
Section: Figmentioning
confidence: 99%
“…During murine infection, B. burgdorferi disseminates hematogenously to multiple organs, including joint, heart, skin, and bladder (18). Previous studies suggested that during its infectious cycle, B. burgdorferi could be exposed to DNA-damaging conditions and agents (19)(20)(21)(22)(23)(24)(25)(26)(27). However, little is known about the pathways used by B. burgdorferi to repair damaged DNA and if these systems are required for infection in mice.…”
mentioning
confidence: 99%
“…Here, the recruitment rate of predator-like immune effector cells is a function of the abundance of prey-like B. burgdorferi, resulting in rapid recruitment of immune effector cells and removal of B. burgdorferi when B. burgdorferi population sizes are large, followed by fewer immune effector cells and reduced killing when B. burgdorferi is rare [33]. The recruitment and depletion of immune effector cells such as neutrophils, macrophages and eosinophils have been empirically shown to impact on B. burgdorferi infections within hosts [36][37][38]. Model 3 also predicts continuous fluctuations in B. burgdorferi populations throughout the early stages of infection (Fig.…”
Section: Discussionmentioning
confidence: 99%